Attribute Geometrical Seismic for Fault Identifiction on Canada Exploration Field - Agustiani, Reni; Hiskiawan, Puguh; Rano, Rano (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2016)
It has been performed data interpretation of 3D seismic data and drilling field exploration wellsBasin Nova ScotiaKanada to know structure fault on the field Missisauga Formation. Seismic dataused is 601 inline, crossline 482, and the data used drilling wells are two wells which there is a loggamma ray, sonic logs and log RHOB. Interpretation is done the analysis of the map in thestructure of time and analysis of seismic attribute maps based on the geometrical attribute serves todetermine their structure or structural faults of the data volume 3D. Based on the time structuremap well known that first well is in the region heights and second wells is in low region. Based oninterpretation of the map attributes known three faults are two major fault and one minor fault.Two faults are in the East Sea drilling wells and a small fracture that was on its western side. Thethree fults are directed from Northwest to the Southeast. Fault is expected to serve as ahydrocarbon trap in the area that will be accumulated in drilling wells. Keywords: geometrical attribute, Seismic data, drilling wells, time structure map.